Landscape perception : linking physical monitoring data to perceived landscape properties - Hedblom, Marcus (2021)
Changes in the landscape affect not only people’s well-being but also how people perceive and use the landscape. An increasing number of policies have highlighted the importance of conserving a landscape’s recreational and aesthetical values. This study develops and evaluates a model that links people’s perceptions of a mountain landscape to physical monitoring data. Using a questionnaire, we revealed how respondents working with the Swedish mountains characterise the Magnificent Mountain landscape (as defined by Swedish policy objectives) and translated these characteristics into data from the National Inventory of Landscapes in Sweden (NILS). We found 14 potential indicators that could be derived from the existing NILS physical monitoring data and which could be used to monitor changes in the landscape values as perceived by people. Based on the results, we suggest how to simultaneously utilise field sampling of physical data and field photos to provide temporal information about landscape perception.